Research Progress of Interfacial Modification of Copper/Diamond Composites for Electronic Packaging - Hu, Zhihua; Zhang, Bowen; Yu, Hongmei; Lei, Yan; Xiong, Haiyan; Jiang, Binghua; Chen, Deping (International journal of thermophysics, 2025)
Copper/diamond composites exhibit significant potential in various fields, including microelectronics, weaponry, power batteries and aerospace, owing to their adjustable transport properties, high thermal conductivity (TC), and customizable coefficients of thermal expansion. However, interface gaps and weak bonding have significantly impeded the application of copper/diamond composites with high thermal conductivity. This paper summarizes the preparation methods and research advancements in the interfacial modification of copper/diamond composites. Revealing that the introduction of carbide-forming elements (e.g., Zr, Cr, Ti) via matrix alloying or diamond surface metallization significantly improves solid–liquid wettability (reducing contact angles below 90°) and enhances interfacial bonding through chemical reaction or atomic diffusion. These insights are crucial for enhancing the interfacial bonding between copper and diamond, thereby improving the thermal conductivity of the composites.